Review of Economics and Statistics over the Past 100 Years: Content Explorer - Khwaja, Asim I.; Mangal, Kunal (The Review of Economics and Statistics, 2019)
March 01 2019 Review of Economics and Statistics over the Past 100 Years: Content Explorer Asim I. Khwaja, Asim I. Khwaja Search for other works by this author on: This Site Google Scholar Kunal Mangal Kunal Mangal Search for other works by this author on: This Site Google Scholar Author and Article Information Asim I. Khwaja Kunal Mangal Online Issn: 1530-9142 Print Issn: 0034-6535 © 2019 The President and Fellows of Harvard College and the Massachusetts Institute of Technology2019The President and Fellows of Harvard College and the Massachusetts Institute of Technology The Review of Economics and Statistics (2019) 101 (1): i–iii. https://doi.org/10.1162/rest_e_00816 Cite Icon Cite Permissions Share Icon Share Facebook Twitter LinkedIn MailTo Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Search Site Citation Asim I. Khwaja, Kunal Mangal; Review of Economics and Statistics over the Past 100 Years: Content Explorer. The Review of Economics and Statistics 2019; 101 (1): i–iii. doi: https://doi.org/10.1162/rest_e_00816 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsThe Review of Economics and Statistics Search Advanced Search This content is only available as a PDF. © 2019 The President and Fellows of Harvard College and the Massachusetts Institute of Technology2019The President and Fellows of Harvard College and the Massachusetts Institute of Technology Article PDF first page preview Close Modal You do not currently have access to this content.